Family Separation and Incarceration: an Intersectional Analysis of the Carceral System - (:unkn) unknown (My University, 2020)
Through an intersectional, feminist, prison abolitionist framework, this thesis investigates the types of reentry services available to formerly incarcerated women-identifying people in Milwaukee, Wisconsin and the challenges they face during the reentry process, particularly as they relate to gender-based violence and family separation. Based on qualitative research methods, including discourse analysis and content analysis of 33 reentry service providers (RSPs) in the Milwaukee-area in addition to two interviews with formerly incarcerated cis-women and two Wisconsin Department of Corrections employees, key findings reveal how raced, gendered, and classed assumptions influence the type of reentry services available. I argue that the failure to include women-identifying people in reentry services is a form of gender-based violence that further expands the scope of the gendered and heteronormative carceral state (Shaylor & Miners, 2013). This thesis concludes with a consideration of strategies to create, and build on, an abolitionist future in Milwaukee, WI, specifically through non-reformist reforms (Gilmore, 2017). By centering healing, community accountability, and transformative justice, we invest in practices that build the type of world we want to live in without relying on policing apparatuses and carceral regimes.
Keywords: carcerality; Milwaukee; Wisconsin; prison abolition; reentry services